Plant polyphenols can directly affect ovarian cell functions and modify toluene effects. Issue 1 (14th October 2020) - Sirotkin, Alexander; Záhoranska, Zuzana; Tarko, Adam; Fabova, Zuzana; Alwasel, Saleh; Halim Harrath, Abdel
Abstract: The influence of toluene alone and in combination with plant polyphenols apigenin, daidzein or rutin on viability, proliferation (proliferating cell nuclear antigen accumulation), apoptosis (Bax accumulation) and release of progesterone (P), testosterone (T) and estradiol (E) in cultured porcine ovarian granulosa cells was evaluated. Toluene reduced ovarian cell viability, proliferation and E release; it promoted P release, demonstrating no effect on apoptosis or T output. Apigenin alone failed to affect cell viability, proliferation, apoptosis and P and T release, but stimulated E release, promoting the inhibitory action of toluene on proliferation, preventing and even reversing the stimulatory effect of toluene on apoptosis and P. Daidzein alone reduced cell viability and promoted T release, preventing and reversing the stimulatory effect of toluene on cell proliferation. Rutin administration reduced cell viability and E output, promoting the inhibitory action of toluene on cell viability and stimulatory effect on P release, and preventing the inhibitory action of toluene on E release. Toluene reduced apigenin‐ and rutin‐induced E release, promoting action of daidzein on cell viability. These observations suggest the action of toluene and plant polyphenols on ovarian cell functions and the functional interrelationships between these molecules in the ovary.